Hulled wheats: A review of nutritional properties and processing methods - Hammed, Ademola Monsur; Simsek, Senay (AACC International, 2014)
There is renewed interest in adopting hulled wheats (emmer, einkorn, and spelt) into our food system, because of their nutritional qualities and improved organoleptic properties. Current research findings have been concisely put together in this review to show the extent of the current and past work in this area and suggest additional research areas. Breeding programs for hulled wheats have received a great deal of attention, and their research findings have shown potential to generate genotypes with improved qualities. More work is required to investigate the changes in nutritional and structural composition of hulled wheats during and after processing and to develop suitable processing methods.